Isolation of secondary metabolite compounds of Coffee Benalu leaves (Loranthus parasiticus (L.) Merr.) and its antibacterial activity test - Destria Roza; Nova Betria Sinaga; Christesya Ambarita (Jurnal Pendidikan Kimia (JPKim), 2022)
Coffee parasite leaves (Loranthus parasiticus (L.) Merr) is one of the plants that can be used as a medicinal material commonly obtained in various subtropical regions or tropical regions. This study aims to isolation of secondary metabolite compounds from methanol extract of coffee leaves and antibacterial activity by of disc diffusion and microdilution methods against S. aureus bacteria, S. mutans, and S. viridians. The result of antibacterial activity against S. aureus bacteria, S. mutans, and S. viridians respectively is 7.5 mm; 7.9 mm; and 8 mm which indicates that the ability to inhibit the growth of methanol extract bacteria 1% coffee leaves belongs to the medium category. The results of the microdilution method in determining the value of KHM against bacteria S. Aureus, S. Mutans, and S. Viridians are equal to the KHM value of 5000 μg/mL. Meanwhile, the MBC value for S. aureus was >5000 g/Ml, for S. mutans was >5000 g/mL and for S. viridians it was 5000 g/mL, indicating that the methanol extract of the coffee parasite leaves was only an inhibitor. Isolation of secondary metabolite compounds is carried out by fractionation using Liquid Vacuum Chromatography and Gravitational Column Chromatography which are further characterized using the GC-MS instrument. The results of the isolation of secondary metabolites from the methanol extract of the leaves of the coffee parasite (Loranthus parasiticus (L.) Merr.) showed that the leaves of the coffee parasite contained any 9 compounds.Keywords:Antibacterial, Diethyltoluamide, Isolation, Loranthus parasiticus (L.) Merr.